ICT loves agglomeration The urban impacts of ICT in the Netherlands - Otto Raspe; Frank Van Oort (European Regional Science Association (ERSA), 2004)
Information and Communication Technology (ICT) has had an undeniable impact on our society. Some people argue that technology has projected us onto a new wave of social and cultural change. Nevertheless, despite the growth of technology and the social significance of its applications, we have only a poor grasp of its actual impact on the use of physical space. The key question addressed in this paper is therefore: how will ICT influence the spatial-economic patterns of business activities in the Netherlands? In offering answers to this question, the paper develops a conceptual framework that distinguishes two roles of ICT in spatial-economic development: that of a `motor', enhancing productivity and encourages the development of economic sectors, and that of an `enabler' (of e-work, e-commerce and e-business), which may lead households and firms to adopt a different attitude to space requirements. The paper is based on a thorough survey of the current literature on the subject, the results of a recent survey of ICT's impact on society, and original empirical research into specific factors such as ICT companies' location preferences and the willingness of knowledge workers to commute. The paper presents an assessment of the usefulness of these concepts in terms of the Dutch situation, both today and in the future. We conclude that Information and Communication Technology has not yet had a marked visible impact on the use of space. To the contrary, despite predictions neither Dutch companies (particularly those in the ICT sector) nor knowledge workers display any unusual degree of mobility at the local or regional s 2perfect substitute for `traditional' behavioural patterns. Nevertheless, there are clear indications that the `spatial order' of the Netherlands is likely to change. Although it is likely that ICT will consolidate underlying spatial patterns, on the regional aggregate changes are occurring within those patterns. While (inner) cities have traditionally been the breeding ground for new ICT companies, this function has now largely been taken over by the outlying city regions, in which multiple clusters of economic activity are emerging: a process of `splintering urbanism'. However, despite this regionalized pattern of deconcentration, the traditional city centres continue to fulfil a number of essential functions. These centres remain the meeting places, and the shopping and entertainment centres for businesses and households (the `Consumer City'). In the processes of deconcentration and multimodality, ICT should be seen to play an important facilitating and strengthening role. cale. ICT does not function as a 2perfect substitute for `traditional' behavioural patterns. Nevertheless, there are clear indications that the `spatial order' of the Netherlands is likely to change. Although it is likely that ICT will consolidate underlying spatial patterns, on the regional aggregate changes are occurring within those patterns. While (inner) cities have traditionally been the breeding ground for new ICT companies, this function has now largely been taken over by the outlying city regions, in which multiple clusters of economic activity are emerging: a process of `splintering urbanism'. However, despite this regionalized pattern of deconcentration, the traditional city centres continue to fulfil a number of essential functions. These centres remain the meeting places, and the shopping and entertainment centres for businesses and households (the `Consumer City'). In the processes of deconcentration and multimodality, ICT should be seen to play an important facilitating and strengthening role.
Keywords: 330